Emotion dysregulation and depressive symptoms mediate the association between inhibitory control difficulties and aggressive behaviour in children with ADHD - Marques, Sofia; Correia-de-Sá, Teresa; Guardiano, Micaela; Sampaio-Maia, Benedita; Ferreira-Gomes, Joana (Frontiers in Psychiatry, 2024)
Background/objectives Impulsive aggressive behaviour, although not a core symptom, is often part of the clinical presentation of attention-deficit/hyperactivity disorder (ADHD). Recently, impulsive aggression has been attributed to emotion dysregulation, which is currently conceptualised as a transdiagnostic factor and seems to contribute to the co-occurrence of other problems in ADHD. Thus, this study investigated the presence of impulsive aggressive behaviour and explored whether emotion dysregulation mediates the relationship between inhibitory control difficulties and aggressive behaviour in children with ADHD. Because ADHD may act as a risk factor for the development of other conditions, such as internalising problems, we aimed to understand whether depressive symptoms contribute to this relationship. Methods Seventy-two children were recruited from a hospital and the community, 38 of whom had ADHD and 34 were typically developing (TD). Parents completed the Child Behaviour Checklist, the Behaviour Rating Inventory of Executive Function, and the Emotion Regulation Checklist. Simple mediation and serial mediation models were performed to test our hypotheses. Results Aggressive behaviour was significantly higher in ADHD children compared to TD children. Emotion dysregulation fully mediated the relationship between inhibitory control difficulties and aggressive behaviour in ADHD children. Adding depressive symptoms to the model increased the explained variance in aggressive behaviour. Conclusion The main result of our study supports the role of emotion dysregulation and depressive symptoms in mediating the relationship between inhibitory control difficulties and impulsive aggressive behaviour in children with ADHD. This highlights that aggressive behaviour is, in part, a result of the inability of the child to appropriately regulate their emotions. Future interventions may be tailored to improve emotion regulation skills to address aggressive behaviour.